Kinetic modelling of alkyl ketene dimer hydrolysis during the storage and papermaking process. (17th February 2019) - Yan, Ning; Wan, Xiao‐Fang; Hu, Hui‐Chao; Chai, Xin‐Sheng
Abstract: An investigation of the hydrolysis of diluted alkyl ketene dimer (AKD) dispersion was carried out under different conditions from which a kinetic model for predicting the AKD hydrolysis during its storage and papermaking process was proposed. As observed, the higher pH, elevated temperature, and longer time can accelerate the hydrolysis of AKD in the water medium. The results showed that the proposed model could provide a satisfactory description of AKD hydrolysis at various conditions, in which the R‐squared of the correlation coefficient (R 2 ) between the measured and predicted data was 0.978. Based on this model, a successful controlling strategy aimed at optimizing the chemical efficiency in the practical application can be determined. Abstract : The hydrolysis kinetics of alkyl ketene dimer dispersion under different conditions was conducted by determining the AKD hydrolysis product CO2 with the headspace‐gas chromatographic technique. The higher pH, elevated temperature, and longer time can accelerate the hydrolysis of AKD in the water medium. The proposed model provided a satisfactory description of AKD hydrolysis during its storage and papermaking process.